Multi-agent based load balancing in cloud computing - Sandeep Kumar, S; Tarun Kumar, S; Sathraja, G; Nagatejasri, J (International Journal of Engineering and Technology, 2017)
Cloud knowledge centers area unit usually comprised of multiple servers with doubtless completely different specifications and unsteady resource usages. The challenge for these data centers is how to handle and service the millions of Requests such that the Quality of the ser-vice (Qos) is not compromised. Load balancing is an important aspect in cloud computing that involves an even work distribution among the available machines such that no machine is overloaded. This work discusses on numerous Agent primarily based load equalization tech-niques capableof equalization workloads across multiple servers to provide customer Satisfaction and economical Resource Utilization. We propose a Dynamic Multi-Agent based algorithm to address the load balancing issue .In this, we describe about Agents and how they can be used to solve load balancing in cloud computing.Â Â